Public health implications of multidrugresistant and methicillinresistant Staphylococcus aureus in retail oysters - Rahma Mohammed; Sara M. Nader; Dalia A. Hamza; Maha A. Sabry (Scientific Reports)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) is a major challenge for food safety and public health. This study aimed to investigate the potential role of oysters sold in Egypt as a source for Staphylococcus aureus (S. aureus), MRSA, and multidrug-resistant methicillin-resistant Staphylococcus aureus (MDR-MRSA). It also examined the occurrence of tsst-1 virulence gene and assessed the associated zoonotic risks. Thirty-three pooled fresh oyster samples were acquired from different retail fish markets in Egypt. S. aureus was identified by conventional culture-based and molecular methods. Antimicrobial resistance was performed by the disk-diffusion method, and the multiple antibiotic resistance index (MARI) was calculated. Antimicrobial resistance (mecA and mecC) and virulence (tsst-1) genes were screened using polymerase chain reaction. The clustering of virulent MDR-MRSA isolates was performed using R with the pheatmap package. The prevalence of S. aureus was 39.4% (13 /33), and 77% of them (10/13) were classified as MDR with MARI values greater than 0.2. Notably, 46.2% (6 /13) of isolates were identified as MRSA and all MRSA isolates displayed MDR. Of the MDR-MRSA isolates, 66.7% (4 /6) possessed the mecA gene, while 16.7% (1 /6) tested positive for the mecC gene. Additionally, the tsst-1 gene was identified in one isolate (16.7%). Interestingly, two MDR-MRSA isolates exhibited a clustered pattern. The study sheds light on the emergence of virulent MDR-MRSA isolates in Egyptian oysters. It highlights oysters as a potential source for spreading these isolates within aquatic ecosystems, posing a threat to food safety and public health.